Comparing sensitivity and specificity of rapid antigen test (ATK) with standard RT-PCR - Laoluekiat, Somjate (Journal of Preventive Medicine Association of Thailand, 2023)
Gold standard of COVID-19 detection is the detection of viral genetic material by Reverse Transcription – Polymerase Chain Reaction (RT-PCR), which takes long testing time (3-5 hrs.). Rapid Screening Kit (Antigen test kit; ATK) (Thai FDA standard) can report the result faster, but there is an issue on sensitivity and specificity. This study tested the sensitivity and specificity of ATK compared to RT-PCR. The second objective was to increase sensitivity and specificity of ATK by adding screening symptoms together with ATK. This retrospective study was conducted from medical records of COVID-19 patients in Paholpolpayuhasena Hospital, Kanchanaburi Province, between January 1, 2021 to May 31, 2022. A total of 668 participants, 410 of them (61.4%) were diagnosed with COVID-19. 281 (42.1%) had abnormal chest X-ray. Mean age was 50 years. Most of them had normal vital signs. Most common symptoms were fever, tiredness, cough and sore throat, but no conjunctivitis, tongue and joint pain were noted. Two methods had the same results in 616 patients (92.2%). Sensitivity of the rapid screening method (ATK) alone was 91.8% and specificity was 92.8%. Sensitivity and specificity were increased when added symptoms in screening criteria. Sensitivity increased to 94.7% and specificity increased to 99.6% The efficacy of the rapid screening kit (ATK) is highly effective compared to the standard assay (RT-PCR), especially if used in the epidemic phase. A high incidence of the disease increases the likelihood of a positive predictive value of the disease, eliminating the need for more time-consuming and costly standard RT-PCR methods. In addition, if there is a concern in the false negative ATK, second serial RT-PCR could be offered to patients. However, this study was done in hospital setting, the ATK results may be varies for self ATK testing.